Blockade of CRF1 receptors in the central nucleus of the amygdala attenuates the dysphoria associated with nicotine withdrawal in rats - Bruijnzeel, Adrie W. (2011)
The majority of smokers relapse during the acute withdrawal phase when withdrawal symptoms are most severe. The goal of the present studies was to investigate the role of corticotropin-releasing factor (CRF) and noradrenergic transmission in the central nucleus of the amygdala (CeA) in the dysphoria associated with smoking cessation. It was investigated if blockade of CRF1 receptors, blockade of α1-adrenergic receptors, or stimulation of α2-adrenergic receptors in the CeA diminishes the deficit in brain reward function associated with nicotine withdrawal in rats. Nicotine dependence was induced by implanting minipumps that delivered a nicotine solution. Withdrawal was precipitated with the nicotinic acetylcholine receptor antagonist mecamylamine. A discrete-trial intracranial self-stimulation procedure was used to assess the negative affective aspects of nicotine withdrawal. Elevations in brain reward thresholds are indicative of a deficit in brain reward function. In all the experiments, mecamylamine elevated the brain reward thresholds of the rats chronically treated with nicotine and did not affect the brain reward thresholds of the saline-treated control rats. Intra-CeA administration of the CRF1 receptor antagonist R278995/CRA0450 completely prevented the mecamylamine-induced elevations in brain reward thresholds in the nicotine-treated rats and did not affect the brain reward thresholds of the saline-treated control rats. R278995/CRA0450 has also been shown to block sigma-1 receptors but there is no evidence that this could affect negative mood states. Intra-CeA administration of the α1-adrenergic receptor antagonist prazosin or the α2-adrenergic receptor agonist clonidine did not affect the brain reward thresholds of the nicotine or saline-treated rats. These studies suggest that CRF1 receptor antagonists may diminish the dysphoria associated with smoking cessation by blocking CRF1 receptors in the CeA.